Diffuse Idiopathic Skeletal Hyperostosis with Cervical Vertebra Involvement: A Case Report - Mehmet Arslan; Halil Öğüt; Hayal Güler; Ayşe Dicle Turhanoğlu (Galenos Yayinevi, 2021)
Diffuse idiopathic skeletal hyperostosis is a non-inflammatory disease characterized by ossification and calcification in soft tissues, such as enthesis and joint capsules. The thoracic vertebra is often affected; however, cervical vertebra involvement can also be seen. Diagnosis is made by observing ossifications in the anterior surface of the four vertebrae and excluding spinal degenerative and inflammatory diseases. Pain and movement limitation is frequently observed in cervical vertebra involvement, but symptoms, such as dysphagia, hoarseness, and snoring, may also occur. This study aimed to present a 69-year-old male patient with pain in the neck and back, movement limitations, and swallowing difficulties, mostly with solid foods. The cervical imaging of the patient revealed anterior ossifications that compress the esophagus and posterior ossifications without myelomalacia. Surgery was recommended to the patient for his progressive dysphagia but was refused. Partial improvement was achieved in the patient's complaints with exercise and swallowing training in pain, movement limitation, and swallowing difficulties.